(x-1/2)\(^2\)=9/25
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1: \(\left(3x-\dfrac{1}{5}\right)^2=\left(-\dfrac{3}{25}\right)^2\)
=>3x-1/5=3/25 hoặc 3x-1/5=-3/25
=>3x=8/25 hoặc 3x=2/25
=>x=8/75 hoặc x=2/75
2: \(\left(2x-\dfrac{1}{3}\right)^2=\left(-\dfrac{2}{9}\right)^2\)
=>2x-1/3=2/9 hoặc 2x-1/3=-2/9
=>2x=5/9 hoặc 2x=1/9
=>x=5/18 hoặc x=1/18
1.\(\left(\dfrac{1}{3}-x\right)^2=\dfrac{9}{25}\Leftrightarrow\left[{}\begin{matrix}\dfrac{1}{3}-x=\dfrac{3}{5}\\\dfrac{1}{3}-x=-\dfrac{3}{5}\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{4}{15}\\x=\dfrac{14}{15}\end{matrix}\right.\)
2.\(\left(5-x\right)^2=25\Leftrightarrow\left[{}\begin{matrix}5-x=5\\5-x=-5\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=10\end{matrix}\right.\)
`1, -2/9 xx 15/17 + (-2/9) xx 2/17`
`= -2/9 xx (15/17 + 2/17)`
`= -2/9 xx 17/17`
`=-2/9xx1`
`=-2/9`
__
`-5/3 xx 6/5 + (-7/9) xx 3/10`
`= -30/15 + (-21/90)`
`= -2 + (-7/30)`
`=-60/30 +(-7/30)`
`=-67/30`
__
`15/20 xx 7/5 + (-9/7) xx (-6/4)`
`=3/4 xx7/5 + (-9/7) xx(-6/4)`
`= 21/20 + 54/28`
`= 21/20 + 27/14`
`=417/140`
__
`-25/13 xx 5/19 + (-25/13) xx 14/19`
`=-25/13 xx (5/19 +14/19)`
`=-25/13 xx 19/19`
`= -25/13 xx 1`
`=-25/13`
__
`-7/13 xx 13/5 + (-9/7) xx 5/3`
`=-7/5 +(-15/7)`
`=-124/35`
a: =>12/25:x=9/25-1/5=4/25
=>x=3
b: =>8/17x=10/27-2/9=10/27-6/27=4/27
hay x=17/54
G(x) = 8(x + 1)³ + 1
G(x) = 0
⇒ 8(x + 1)³ + 1 = 0
8(x + 1)³ = -1
(x + 1)³ = -1/8
(x + 1)³ = (-1/2)³
x + 1 = -1/2
x = -1/2 - 1
x = -3/2
Vậy nghiệm của G(x) là x = -3/2
H(x) = 8/9 - 2((x - 1)²
H(x) = 0
⇒ 8/9 - 2(x - 1)² = 0
2(x - 1)² = 8/9
(x - 1)² = 8/9 : 2
(x - 1)² = 4/9
x - 1 = 2/9 hoặc x - 1 = -2/9
*) x - 1 = 2/9
x = 2/9 + 1
x = 11/9
*) x - 1 = -2/9
x = -2/9 + 1
x = 7/9
Vậy nghiệm của H(x) là x = 7/9; x = 11/9
1. (x^2-25)^2-(x-5)^2
=(x-5)2(x+5)2-(x-5)2
=(x-5)2.[(x+5)2-1)
=(x-5)2.(x+5-1)(x+5+1)
=(x-5)2.(x+4)(x+6)
2. (4x^2-25)^2-9(2x-5)^2
=(2x-5)2(2x+5)2-9.(2x-5)2
=(2x-5)2[(2x+5)2-9]
=(2x-5)2(2x+5-3)(2x+5+3)
=(2x-5)2(2x+2)(2x+8)
=4(2x-5)2(x+1)(x+4)
+) <=>\(\orbr{\begin{cases}x-1=\frac{3}{2}\\x-1=\frac{-3}{2}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{5}{2}\\x=-\frac{1}{2}\end{cases}}}\)
+) <=>\(\orbr{\begin{cases}x-1=\frac{5}{3}\\x-1=-\frac{5}{3}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{8}{3}\\x=-\frac{2}{3}\end{cases}}}\)
(x-1/2)2=9/25
(x-1/2)2=(3/5)2
x-1/2=3/5
x=11/10
(x-1/2)^2=(3/5)^2
x-1/2=3/5
x=11/10